Fragments: Exploring waste-based concrete from construction and demolition waste - Tantipisanu, Bongkodpast (My University, 2023)
The generation of solid waste is an inevitable outcome of societies that have undergone industrialization. Economic growth has been observed to lead to a rise in the production of solid waste, which is typically disposed of in landfills and has been found to pollute the environment with waste materials, thereby affecting the quality of soil, water, and air. The current scenario is witnessing a surge in the extraction of raw materials to cater to the increasing demand. Simultaneously, the shortage of land-filling areas, rapid industrial expansion, and the adoption of a take-make-waste linear economy have resulted in a twofold increase in waste accumulation. Consequently, they have instigated a worldwide reevaluation of strategies pertaining to the rethinking of waste and its management. The thesis explores the potential of utilizing recycled construction and demolition wastes (CDWs) as alternative materials in conjunction with the geopolymer or alkali-activated materials (AAM) technique. This approach enables the CDWs to function as a binder and be mixed with recycled fine and coarse aggregates, thereby eliminating the need for conventional river sand. Additionally, the use of no more than 10% cement allows for room-temperature curing of the materials. The study aims to evaluate the performance of this approach under real-world conditions; therefore, the experimentation involving binders is conducted with the aim of exploring new possibilities for versatility and composition, thereby facilitating the reevaluation of waste materials. This process is also linked to the unique characteristics of the waste sources and connects with the public to gain understandings of ”waste” or secondary materials amidst rapid urban development. Aiming to focus on the experimentation of manipulating waste-based concrete that can undergo transformation over time and its potential for infinite recyclability. The influence of materials on the design of a building and the ways in which architects can utilize them to foster social connections and a sense of community where waste is sorted through waste-based pavilions The present study aims to investigate the ways in which architects can make well-informed decisions regarding the materials they utilize, taking into account the properties and lifecycle impacts of such materials.
Keywords: Waste-based concrete; Construction and demolition wastes; Recycled aggregates; Geopolymer